Functional Impairment and Quality of Life in Patients with Obsessive Compulsive Disorder - Sahoo, Puspita (Indian J Psychol Med, 2017)
BACKGROUND: This study was carried out to enumerate the level of difference in functional impairment and quality of life (QOL) in obsessive-compulsive disorder (OCD) patients and normal control group to find out the relationship among ICD functional impairment and QOL. METHODOLOGY: Thirty patients diagnosed with OCD as per International Classification of Diseases Diagnostic Criteria for Research-10 were taken for study. The control group consists of 30 normal participants from the community. Functional impairment and QOL questionnaires were administered on both groups to measure functional impairment and QOL in OCD. RESULTS: The mean age of onset of OCD was (23.8 ± 7.25), mean duration of illness was (6.3 ± 4.47), and mean duration of treatment was (2.56 ± 2.47). It was also observed that total score as well as all the domains of the World Health Organization QOL-BREF, OCD patients scored significantly less (P < 0.001) compared to normal controls. Dysfunctional Analysis Questionnaire (DAQ)-Social area and DAQ-Personal area had statistically significant positive correlation (P < 0.05) with an obsessive subscale of Yale–Brown Obsessive Compulsive Scale (Y-BOCS) whereas DAQ-social area (P < 0.05), DAQ-Personal Area (P < 0.05) had statistically significant positive correlation with a total score of Y-BOCS. CONCLUSION: The presence of functional impairment leads to poor QOL in the persons with OCD.